Wyzwania w realizacji projektów europejskich - waloryzacja, dyseminacja, eksploatacja - Clijsters, Willy (EU-Projects : Valorisation, Dissemination, Exploitation - the Impossible Challenge?, 2008)
The EU expressed the strong will to be the most competitive economy of the world (declaration of Lisbon). Therefore fundamental and applied scientific research is one of the most important levers. Universities, as one of their main missions is high quality research, are intensively appealed. Many of them, if not most, are actively involved in different EU-programs. But universities are not familiar how to disseminate, how to market their findings and in general their expertise. But since in democratic nations citizens want to know and to evaluate the use of their taxes, since the needs of societies are continuously growing and since the possibilities (the finances) of each society are limited, an acceptable balance has to been found between wishes and reality and users of public money have to respond its use. This rationale generates a big problem for universities while they have a lack of market orientation: no strategy, no experience, no market skills. This is especially true for new EU-LLP-projects, where an elaborated and detailed dissemination plan has to be included in a project proposal. Which possibilities have partners of LLP-projects for the dissemination of their products? Which is the most current situation until now? What has been done in ICSME? Which perspectives for the near and far future?
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 135-140